Increasing teachers’ technological skills with a nationwide project - Boateng, Christina [Interviewter]; Olesen, Julia [Interviewer] (My University, 2022)
„Christina Boateng, Senior Lecturer at the University of Cape Coast, and Julia Olesen, senior technical adviser and project manager at the German Office for International Cooperation (GOVET) at the Federal Institute for Vocational Education and Training (BIBB) in Germany, reflect on the impact of the COVID-19 pandemic on Technical Vocational Education and Training (TVET) in Ghana and on how digital competences of training personnel can be increased. “ (author’s abstract; BIBB-Doku)
Keywords: P 3.2 Lehrpersonal; I 2.3.1 Afrika; 370; Berufsbildung; Technische Bildung; Bildungspersonal; Digitalkompetenz; Qualifizierung; Pandemie; Ghana